2015
DOI: 10.1007/s10040-015-1286-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimal management of saltwater intrusion in the coastal aquifer of Malia, Crete (Greece), using particle swarm optimization

Abstract: Saltwater intrusion is a common phenomenon in coastal aquifers that can affect the quality of water intended for drinking and irrigation purposes. In order to provide sustainable management options for the coastal aquifer of Malia, located on the Greek island of Crete, a weighted multi-objective optimization methodology is employed. The methodology involves use of the particle swarm optimization algorithm combined with groundwater modelling. The sharp-interface approximation combined with the Ghyben-Herztberg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Lee et al have explored the seawater intrusion caused by groundwater overexploitation in the coastal plains of Korea [28]. Karatzas et al insisted that in order to control the invasion of sea water, it is necessary to control the production of pumping wells and to find new alternative water sources [29]. Through the use of ground subsidence and depression data, the environmental problems caused by groundwater overexploitation were studied by Shi et al [20].…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al have explored the seawater intrusion caused by groundwater overexploitation in the coastal plains of Korea [28]. Karatzas et al insisted that in order to control the invasion of sea water, it is necessary to control the production of pumping wells and to find new alternative water sources [29]. Through the use of ground subsidence and depression data, the environmental problems caused by groundwater overexploitation were studied by Shi et al [20].…”
Section: Introductionmentioning
confidence: 99%
“…A more complex and data requiring approach is the one that make use of numerical models to deploy new characterization methods, for example, describing the linear and non-linear optimization approaches to manage seawater intrusion via numerical scenarios [144][145][146][147][148][149][150], or determining the long-term effects induced by pumping saline groundwater to feed desalination plants [151]. In addition, the employment of geophysical methods coupled with numerical models to quantify the aquifer salinization extension has been explored only in few studies [152][153][154][155], and only one reported the socio-economic aspects of SWI in the modeling procedure [156].…”
Section: Data Handling Techniquesmentioning
confidence: 99%
“…where arg is the value of argument x of F (x) [10]. By using the solving method of fitness, the particle swarm is initialized randomly in the feasible domain, and the particle with non-dominated solution is selected to construct the elitism set N P i .…”
Section: 1mentioning
confidence: 99%